Analisis Faktor Penyebab Keterlambatan Pengembalian Berkas Rekam Medis Rawat Inap di RS Universitas Airlangga - Abdul Haqqi; Novita Nur Aini; Andri Permana Wicaksono (Politeknik Negeri Jember, 2020)
One of the hospital's obligations is to organize a medical record. Good or bad medical record-up is a description of the quality of the hospital. The minimum service standard for the patient's return of the patient's medical record is completed by obtaining medical services until the medical record file returns to the medical record room within 2x24 hours. The return of an inpatient medical record in Universitas Airlangga Hospital takes more than 2 X 24 hours, even up to 1 week is calculated since the patient returned home and the file has not been completed 100%. Such problems will result in delayed reporting, provision of old patient medical record files should still be sought in the last location of the borrower's medical record file if not found in the filing rack. There is still an unrecorded return time in the expedition book. There is a problem with the delay in the return of an inpatient medical record so that it is necessary to identify the problem that aims to correct or minimize potential problems. The identification methods used are observation and interview methods. Observations are performed on data sources collected either primary data or secondary data related to the cause of the return of the medical record file. The interview is conducted by the researcher to the officer related to the late return of the inpatient medical record file. The study uses the 5M method (Man, Machine, Method, Material, and Money) by Harrington Emerson.